EVALUATION OF A FEEDBACK KIOSK SYSTEM IN A TEACHING HOSPITAL - Serra-Julià, Marcel (My University, 2011)
The practice of medicine has evolved from individual practice, mainly led by physicians, towards an interdisciplinary team-based activity that takes into consideration patients’ needs, preferences and values. This shift towards what is known as the patient-centered care (PCC) model requires better communication among medical staff and patients. Feedback is a key factor to improve team learning processes and also to understand patient perspectives. The objective of this thesis was to create a system to facilitate feedback processes within the Toronto General Hospital (TGH). To do so, a kiosk-based system was designed, allowing patients and health care providers to send feedback messages as well as positive recognition messages in appreciation of other people’s commitments and achievements. A pilot test was conducted by placing a kiosk in the General Internal Medicine unit at TGH for seven weeks. During this study, the application running the kiosk registered all user actions, with the objective of understanding how patients and staff interacted with the system. The kiosk was perceived as a positive, easy to use, and valuable tool by patients and providers. The different elements that need to be improved for future upgrades of the system are discussed. Overall, the use of kiosk-based systems to gather feedback should be considered when creating high performing teams in the health care domain.
Keywords: kiosk; feedback intervention; recognition; Patient Centered Care (PCC); Internal Medicine; patient; Computational Engineering; Health Services Administration; Health Services Research; Computational Engineering